2020
DOI: 10.1111/odi.13651
|View full text |Cite|
|
Sign up to set email alerts
|

Osteopenic effects of high‐fat diet‐induced obesity on mechanically induced alveolar bone remodeling

Abstract: Obesity has become increasingly prevalent. In the past 40 years, the prevalence of obesity has increased from less than 1% to 6%-8% in children, from 3% to 11% in men, and from 6% to 15% in women during the period of 1975(Jaacks et al., 2019. The rise in obesity poses a great threat to human health and has become a major healthcare challenge in all populations (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…The inconsistencies in research findings may be attributed to the heterogeneity between different studies. Studies have shown that serum concentrations of IL-1β, IL-6, TNF-α, and additional pro-inflammatory cytokines increase in obese mice, along with a significant increase in the ratio of nuclear factor-κB receptor activator ligand/osteoprotegerin in periodontal tissues [ 31 ]. Plasma levels of free fatty acids are often higher in obese patients, and these fatty acids can competitively bind to Toll-like receptor (Toll-like receptor, TLR) 2/4, inhibiting host immune defense against pathogens and leading to immune tolerance and dysbiosis of the periodontal microenvironment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistencies in research findings may be attributed to the heterogeneity between different studies. Studies have shown that serum concentrations of IL-1β, IL-6, TNF-α, and additional pro-inflammatory cytokines increase in obese mice, along with a significant increase in the ratio of nuclear factor-κB receptor activator ligand/osteoprotegerin in periodontal tissues [ 31 ]. Plasma levels of free fatty acids are often higher in obese patients, and these fatty acids can competitively bind to Toll-like receptor (Toll-like receptor, TLR) 2/4, inhibiting host immune defense against pathogens and leading to immune tolerance and dysbiosis of the periodontal microenvironment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo studies showed that locally generated bacterial inflammation inhibited RUNX2 expression and up-regulated c-fos and interleukin (IL)-1 β expression levels in osteoblasts induced by tensile strain, and reduced the osteogenesis of osteoblasts under continuous tensile stress ( Lacey et al, 2009 ; Li et al, 2021 ). Obesity induced by high-fat diet decreases osteoblast activity in alveolar bone of the OTM stretching side ( Luo et al, 2021 ). Therefore, it is necessary to consider several factors to maximize the function of osteoblasts using tensile stress.…”
Section: Mechanical Stimulation With Osteoblastsmentioning
confidence: 99%
“…Suppressed osteoblastic marker expression was also observed in NZO osteoblasts including alpha-1 type I collagen, bone gamma-carboxyglutamate protein, and RUNX family transcription factor 2 (Runx2). The HFD-induced model also suggested that obesity downregulated Runx2 in the periodontal area [ 132 ].…”
Section: Mechanisms By Which Obesity Enhances Periodontal Bone Lossmentioning
confidence: 99%
“…Osteoprotegerin (OPG) can block the function of RANKL by competitively binding to RANK. Numerous studies have reported an increased ratio of RANKL/OPG in the periodontal tissue of the obese model, suggesting an activated osteoclast function in the animal [ 132 , 134 ]. The hyperinflammation, increased oxidative stress, and immune cell dysfunction mentioned above can interact with osteoclast formation and function, leading to bone loss.…”
Section: Mechanisms By Which Obesity Enhances Periodontal Bone Lossmentioning
confidence: 99%